A comprehensive review on the health benefits and nutritional significance of fucoidan polysaccharide derived from brown seaweeds in human, animals and aquatic organisms. (15th February 2021) - Saeed, Muhammad; Arain, Muhammad A.; Ali Fazlani, Sarfraz; Marghazani, Illahi B.; Umar, Muhammad; Soomro, Jameela; Bhutto, Zohaib A.; Soomro, Feroza; Noreldin, Ahmed E.; Abd El‐Hack, Mohamed E.; Elnesr, Shaaban S.; Farag, Mayada R.; et al.
Abstract: Fucoidan is a sulphated polysaccharide isolated from brown seaweeds. It has attracted a lot of attention due to its multiple physiological and biological properties. The most dominant polysaccharides in brown seaweeds are laminarin and alginic acid. Fucoidan extracted from brown seaweed possess various biological functions including anti‐inflammatory, immunomodulatory, antitumour, antibacterial, antiviral, anticoagulant, antioxidant, neuroprotective, cardio‐protection and growth‐promoting effects. Dietary supplementation of fucoidan showed significant therapeutic influences on aquatic organisms, human, livestock and poultry. This review highlights the medicinal importance and nutritional values of fucoidan polysaccharides for fish, animals and humans, to be used as a natural agent for the treatment of various pathological disorders and to replace the synthetic antibiotics. Previously, most studies are focused on in vitro model and in mice. Further studies are warranted on in vivo model and focusing on a molecular basis to understand the mechanisms of action of fucoidan as an alternative therapeutic drug for fish, animals and humans. Another objective of this review is to give more light about the beneficial impacts of fucoidan on productive performance of animals and poultry as well as aquatic organisms.